Strain Tracking to Identify Individualized Patterns of Microbial Strain Stability in the Developing Infant Gut Ecosystem - Koo, Hyunmin; Crossman, David K.; Morrow, Casey D. (Frontiers in Pediatrics, 2020)
Stable microbe and host interactions are established during the development of the infant gut microbial community that provide essential functions for the efficient digestion of food, immune development, and resistance to colonization with pathogens. To further delineate the stability of the gut microbial community during this time, we have used microbial strain tracking analysis with published longitudinal metagenomic data sets to identify strains that persist in the developing infant gut ecosystem. In the first study, 17 infants were evaluated that had not received antibiotics for 3 years after birth. An infant specific pattern was seen for stable and unstable microbial strains during this time, with only one infant having no stable strains identified out of available strains during the first 3 years. Strain tracking was also applied to follow microbes in a separate set of 14 infants that had multiple doses of antibiotics over the 3 years. In 10 out of 14 infants given multiple antibiotics during the first 3 years, we identified a unique pattern of transient strains that appeared after multiple antibiotic treatments for a short time compared to that in infants not on antibiotics. In a second, independent study, we selected a subset of 9 infants from a previously published study consisting of high-density longitudinal fecal sampling to analyze the gut microbial strain stability of Bacteroides vulgatus and Bifidobacterium adolescentis for up to 6 years following birth. Individual specific patterns were found consisting of varying dominant microbial strains that were independent of antibiotic exposure and birth mode. Our analysis demonstrates an individual specific inherent variability of extinction and persistence of microbial strains in the infant gut community during a time of development that is critical for interactions necessary for establishing normal metabolism and the development of the host immune response.